Context of the beginning of tobacco use in different social groups (Revista Latino-Americana de Enfermagem, 2014)
OBJECTIVE: analyze contextual aspects of the beginning of tobacco use in different social groups, from everyday representations about the act of smoking. METHODS: five focus groups were conducted to promote discussion about the context of beginning of tobacco use, with groups of people who represented different patterns of social reproduction. The data analysis was based on the theory of social representations, which contextualizes how each group presents the tobacco consumption. RESULTS: the contexts of the beginning of tobacco use were diverse, according to patterns of social reproduction; there were common representations to all groups, but there were also unique representations of each social group. Tobacco is represented as indispensable for groups in unstable social reproduction situations, and as an instrument of pleasure and stress relief for those who can access other material assets. CONCLUSIONS: the study contributed to exposing the concepts on tobacco consumption that are socially disseminated, which can serve as an instrument to planning programs and health actions.